2018
DOI: 10.1073/pnas.1719645115
|View full text |Cite
|
Sign up to set email alerts
|

Chloroplast SRP43 acts as a chaperone for glutamyl-tRNA reductase, the rate-limiting enzyme in tetrapyrrole biosynthesis

Abstract: Assembly of light-harvesting complexes requires synchronization of chlorophyll (Chl) biosynthesis with biogenesis of light-harvesting Chl a/b-binding proteins (LHCPs). The chloroplast signal recognition particle (cpSRP) pathway is responsible for transport of nucleus-encoded LHCPs in the stroma of the plastid and their integration into the thylakoid membranes. Correct folding and assembly of LHCPs require the incorporation of Chls, whose biosynthesis must therefore be precisely coordinated with membrane insert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
68
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 51 publications
(76 citation statements)
references
References 57 publications
(101 reference statements)
8
68
0
Order By: Relevance
“…This theory is upheld in another recent study in which cpSRP43 has been identified as a chaperone for glutamyl-tRNA reductase (GluTR), the rate-limiting enzyme in tetrapyrrole biogenesis (49). Tetrapyrrole is at the core of chlorophyll and the biogenesis of chlorophyll is coordinated with that of LHCPs in order for the proper assembly of lightharvesting complexes to proceed (49). Here they found that a deficit of cpSRP43 as well as…”
Section: Cpsrp43 Protects Hfgf1 and Lysozyme From Heat-induced Aggregmentioning
confidence: 95%
See 4 more Smart Citations
“…This theory is upheld in another recent study in which cpSRP43 has been identified as a chaperone for glutamyl-tRNA reductase (GluTR), the rate-limiting enzyme in tetrapyrrole biogenesis (49). Tetrapyrrole is at the core of chlorophyll and the biogenesis of chlorophyll is coordinated with that of LHCPs in order for the proper assembly of lightharvesting complexes to proceed (49). Here they found that a deficit of cpSRP43 as well as…”
Section: Cpsrp43 Protects Hfgf1 and Lysozyme From Heat-induced Aggregmentioning
confidence: 95%
“…GluTR-binding protein (GBP) significantly reduced production of GluTR and lead to a reduction in chlorophyll biogenesis which suggests that both cpSRP43 and GBP play distinct roles in the stabilization of GluTR (35). This group was able to form a ternary complex between cpSRP43, L18 and GluTR allowing them to speculate that both substrates are not competing for the same binding surface on cpSRP43 (49). Upon further examination, cpSRP43 was found to interact with the N-terminal of GluTR (49).…”
Section: Size Exclusion Chromatography Reveals An Interaction Betweenmentioning
confidence: 98%
See 3 more Smart Citations